Social Media Trends Indonesian and Philippine Communities on Limiting Social Mobility during the Covid-19 Pandemic Period - Wahdania Suardi; Achmad Nurmandi; Eko Priyo Purnomo; Samantha Benedictos (International Journal of Advanced Science and Technology, 2020)
This article discusses the Social Media Trends of Indonesian and Philippine communities related to the phenomenon of the use of social media during the Covid-19 period and also the response of the public to social media about the Limitation of Social Mobility in the Covid-19 Pandemic Period. This research method is a descriptive study by presenting a discussion obtained based on primary sources that are displayed from the results of reduction and display data using social media hashtag analysis from Keyhole in addition to this research data is also supported by observation and literature review. Data analysis activities are data reduction, data presentation, and drawing conclusions. The analysis shows that social media trends regarding mobility restrictions are more frequently discussed in the Philippines than in Indonesia for Transit Stations, Retail & Recreation, Grocery & Pharmacy, Parks, and Workplaces. The highest mobility is limited to the two countries, the Transit Stations. Another interesting discussion is Social Media Trends which are colored with fake news or hoaxes during the Covid-19 epidemic. Deceptive information or hoax news that is spread through social media causes panic in the community. Digital public literacy is still low, especially in the use of social media, which can exacerbate the spread of rumors that cannot be accounted for, therefore the government needs to be involved in providing interesting information on social media and also involves influencers in helping to provide true and responsible information.